Evaluation of Proximate and Mineral Composition of Biscuit Formulated Using Chayote (Sechium edule) and Mung Bean (Vigna radiata) Flours - Sakung, Jamaludin M.; Nuryanti, Siti; Afadil, Afadil; Pulukadang, Sri Hastuti Virgianti; Maryam, Maryam; Mar’atun, Mar’atun (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study aimed to evaluate the quality of biscuits formulated using chayote and mung bean flours to be used as health food products. METHODS: The thermogravimetric method was used to analyses proximate evaluation for moisture content, the dry ashing method was used to analyses ash content, and the Soxhlet method was used to analyses fat content. Crude protein was measured using the spectrophotometric method, while mineral content was measured using the atomic absorption spectrophotometric method. RESULTS: Proximate analysis obtained the highest water content value in F3 (5.298%) and the lowest in F5 (2.118%). The highest value of ash content was in F1 (2.87%) and the lowest was in F5 (1.42%). The highest value of carbohydrate content was in F5 (59.88%) and the lowest was in F2 (53.68). The highest value of fat content was in F1 (32.64%), and the lowest was in F5 (24.33%). The highest amount of protein content was in F5 (12.25%) and the lowest was in F1 (5.65%). Mineral analysis obtained the highest value of potassium content in F5 (429.12%) and the lowest in F1 (142.22%). The highest value of calcium levels was in F5 (69%) and the lowest was in F2 (26.8%). The highest amount of sodium levels was in F5 (417.39%). The highest iron content value was in F5 (14.06). CONCLUSIONS: The quality of the biscuit products made from chayote flour, green bean flour, and both formulations are in the good category with indicators that are acceptable for human consumption because they have high macronutrients and minerals.